Influence of socioeconomic factors on medically unnecessary ambulance calls - Kubota Katsuaki; Ohshige Kenji; Kawakami Chihiro; Tochikubo Osamu (BMC, 2007)
Abstract Background Unnecessary ambulance use has become a socioeconomic problem in Japan. We investigated the possible relations between socioeconomic factors and medically unnecessary ambulance calls, and we estimated the incremental demand for unnecessary ambulance use produced by socioeconomic factors. Methods We conducted a self-administered questionnaire-based survey targeting residents of Yokohama, Japan. The questionnaire included questions pertaining to socioeconomic characteristics, dichotomous choice method questions pertaining to ambulance calls in hypothetical nonemergency situations, and questions on the city's emergency medical system. The probit model was used to analyze the data. Results A total of 2,029 out of 3,363 targeted recipients completed the questionnaire (response rate, 60.3%). Probit regression analyses showed that several demographic and socioeconomic factors influence the decision to call an ambulance. Male respondents were more apt than female respondents to state that they would call an ambulance in nonemergency situations (p < 0.05). Age was an important factor influencing the hypothetical decision to call an ambulance (p < 0.05); elderly persons were more apt than younger persons to state that they would call an ambulance. Possession of a car and hesitation to use an ambulance negatively influenced the hypothetical decision to call an ambulance (p < 0.05). Persons who do not have a car were more likely than those with a car to state that they would call an ambulance in unnecessary situations. Conclusion Results of the study suggest that several socioeconomic factors, i.e., age, gender, household income, and possession of a car, influence a person's decision to call an ambulance in nonemergency situations. Hesitation to use an ambulance and knowledge of the city's primary emergency medical center are likely to be important factors limiting ambulance overuse. It was estimated that unnecessary ambulance use is increased approximately 10% to 20% by socioeconomic factors.